Answer:
![(3x+4)/(x^2-6x+5)=(-7)/(4(x-1)) +(19)/(4(x-5))](https://img.qammunity.org/2020/formulas/mathematics/high-school/s4dwgaf83o2rx9tafv7nvh0ad61a6dtid3.png)
Explanation:
The given rational expression is:
![(3x+4)/(x^(2)-6x+5) = (3x+4)/((x-1)(x-5))](https://img.qammunity.org/2020/formulas/mathematics/high-school/11efhxof2n48fhkf7qf2akwbyxfgkwo5ir.png)
We can use concept of Partial Fractions to solve this problem. Let,
![(3x+4)/((x-1)(x-5))=(A)/(x-1) +(B)/(x-5)](https://img.qammunity.org/2020/formulas/mathematics/high-school/yh2ss2pr4rahirht5ea4gg9xyrvoao36hz.png)
Multiplying both sides by (x - 1)(x - 5), we get:
![3x+4=A(x-5)+B(x-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ojq5g22am0b3m8o9xeop8a3mv6a0w0o9ru.png)
Substituting x = 5, we get:
![3(5)+4=A(5-5)+B(5-1)\\\\ 15+4=0+4B\\\\ 19=4B\\\\ B=(19)/(4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/yz72vlx2qt29a7rpd3ukwuw2hpb9mne56m.png)
Substituting x = 1, we get:
![3(1)+4=A(1-5)+B(1-1)\\\\ 7=-4A\\\\ A=-(7)/(4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/dtiyvf4l0chtz7h3lxjolbaxjatiho1ry3.png)
Substituting the value of A and B, back in the original equation, we get:
![(3x+4)/(x^2-6x+5)=(-7)/(4(x-1)) +(19)/(4(x-5))](https://img.qammunity.org/2020/formulas/mathematics/high-school/s4dwgaf83o2rx9tafv7nvh0ad61a6dtid3.png)